In vitro evaluation of dual-antigenic PV1 peptide vaccine in head and neck cancer patients. Issue 1 (2nd January 2019) - Chai, San Jiun; Fong, Sammuel Chee Yong; Gan, Chai Phei; Pua, Kin Choo; Lim, Paul Vey Hong; Lau, Shin Hin; Zain, Rosnah Binti; Abraham, Thomas; Ismail, Siti Mazlipah; Abdul Rahman, Zainal Ariff; Ponniah, Sathibalan; Patel, Vyomesh; et al.
ABSTRACT: Peptide vaccines derived from tumour-associated antigens have been used as an immunotherapeutic approach to induce specific cytotoxic immune response against tumour. We previously identified that MAGED4B and FJX1 proteins are overexpressed in HNSCC patients; and further demonstrated that two HLA-A2-restricted 9–11 amino acid peptides derived from these proteins were able to induce anti-tumour immune responses in vitro independently using PBMCs isolated from these patients. In this study, we evaluated the immunogenicity and efficacy of a dual-antigenic peptide vaccine (PV1), comprised of MAGED4B and FJX1 peptides in HNSCC patients. We first demonstrated that 94.8% of HNSCC patients expressed MAGED4B and/or FJX1 by immunohistochemistry, suggesting that PV1 could benefit the majority of HNSCC patients. The presence of pre-existing MAGED4B and FJX1-specific T-cells was detected using a HLA-A2 dimer assay and efficacy of PV1 to induce T-cell to secrete cytotoxic cytokine was evaluated using ELISPOT assay. Pre-existing PV1-specific T-cells were detected in all patients. Notably, we demonstrated that patients' T-cells were able to secrete cytotoxic cytokines upon exposure to target cells expressing the respective antigen post PV1 stimulation. Furthermore, patients with high expression of MAGED4B and FJX1 in their tumours were more responsive to PV1 stimulation, demonstrating the specificity of the PV1 peptide vaccine. Additionally, we also demonstrated the expression of MAGED4B and FJX1 in breast, lung, colon, prostate and rectal cancer suggesting the potential use of PV1 in these cancers. In summary, PV1 could be a good vaccine candidate for the treatment of HNSCC patients and other cancers expressing these antigens.